2016
DOI: 10.1093/ajh/hpw057
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Risk Factors and Pregnancy-Induced Hypertension: The Bogalusa Heart Study

Abstract: Elevated childhood BMI is a significant risk factor for PIH in adulthood, which underscores the importance of body weight control in childhood for prevention of PIH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
(41 reference statements)
2
4
0
Order By: Relevance
“…Overall, studies comparing pregnant and nonpregnant groups indicate pregnancy is associated with higher lipid levels 24 and lower blood pressure, especially early in pregnancy 25 . While our results are consistent with these, other studies have suggested that pre‐pregnancy blood pressure and lipids are associated with hypertensive disorders of pregnancy 26–29 . A recent study following 8899 pregnant women without diagnosed pre‐pregnancy hypertensive disorders found that early pregnancy blood pressures are predictive of hypertensive disorders of pregnancy in the second and third trimesters at a lower threshold than previously used 30 …”
Section: Discussionsupporting
confidence: 86%
“…Overall, studies comparing pregnant and nonpregnant groups indicate pregnancy is associated with higher lipid levels 24 and lower blood pressure, especially early in pregnancy 25 . While our results are consistent with these, other studies have suggested that pre‐pregnancy blood pressure and lipids are associated with hypertensive disorders of pregnancy 26–29 . A recent study following 8899 pregnant women without diagnosed pre‐pregnancy hypertensive disorders found that early pregnancy blood pressures are predictive of hypertensive disorders of pregnancy in the second and third trimesters at a lower threshold than previously used 30 …”
Section: Discussionsupporting
confidence: 86%
“…5 In our study, 83% of the births occurred in this same period, and 17% between 1947 and 1963. Furthermore, multiples, stillbirths, and preterm births were, as expected, more common in preeclamptic pregnancies; preeclampsia was associated with age at menarche 21 and childhood overweight 9 in the expected direction, as well as with a lower probability of having subsequent children. 38 Although older participants had to recall whether they had had preeclampsia several decades after the event, the association with the mother's age at delivery was consistent across birth what allaying concerns about differential misclassification due to education.…”
Section: Limitations Of the Datasupporting
confidence: 68%
“…Women who have experienced preeclampsia (or other hypertensive disorders of pregnancy) have a higher incidence of subsequent cardiovascular disease . Preeclampsia and cardiovascular disease share numerous risk factors, including some that originate in early life, such as low birthweight, childhood overweight, short stature, and early age at menarche …”
Section: Introductionmentioning
confidence: 99%
“…Many studies have correlated high levels of leptin with the appearance of various types of cancer, such as the breast where leptin induces activity in aromatase, an enzyme responsible for transforming other steroids into estrogens within breast tissue, finding receptors for leptin in the breast cancer cells, evidence is also available on the relationship between hyperleptinemia and carcinoma of the colon, esophagus and prostate, representing an important line of research in the relationship between leptin and cancer (Li et al, 2016;Jéquier, 2002).…”
Section: Discussionmentioning
confidence: 99%